Estetyczna przygoda sztuki - Krystyna Wilkoszewska (Jesuit University Ignatianum in Krakow, 2017)
The notion of "art" and its understanding have undergone numerous transformations over the centuries. New trends have appeared. Simultaneously the functions assigned to art have been changing, beginning with those most practical and useful, through the reflection of reality, depicting the diversity of emotions and experiences, the aesthetic function, to "presenting itself". Nowadays art experiences another period of notional transformation. Therefore, a necessity arises to refrain from judgement in favour of formulating new adequate questions and depicting new values carried by contemporary art